Extraction of mangrove component for isolation of triterpenoid saponins via ultrasonic extraction method - Mohd Thorik Firdaus, Abdul Kadir (2010)
Ultrasound-assisted extraction was evaluated as a simpler and more effective alternative to conventional method for isolation of actives compound in plants.Ultrasonic extraction has been widely used for getting bioactive substances from different parts of a number of plants.The ultrasonic enhancement of extraction is attributed to disruption of cell walls,particle size reduction and enhanced mass transfer of the cell content via cavitations bubble collapse.Direct evidences are given,confirming that enhanced hydration process and plant material fragmentations are the primary benefits of sonification.In this paper,a method of ultrasonic-assisted extraction was used to extract total triterpenoid saponins from Ceriops Decandra sp,which have been reported to have several medicinal properties and uses.The extracts were directly determined by colorimetric method without any further treatment.Compared with thermal extraction or soxhlet extraction,ultrasonic extraction only need 15 min to give the highest yield of triterpenoid saponins at 0.9972%, while the other extraction methods need several hours or even more than 3 h and give lower yield. Several factors affecting the ultrasonic extraction rate were also discussed,such as extraction time,temperature and ratio of solvent to material.Optimal conditions of ultrasonic extraction can be concluded as follows: 30 min at 70˚C, the ratio of solvent to material is 25 ml/g by using 95% ethanol as the solvent.